2003
DOI: 10.1212/01.wnl.0000055874.24000.4a
|View full text |Cite
|
Sign up to set email alerts
|

Benign adult familial myoclonic epilepsy

Abstract: Benign adult familial myoclonic epilepsy (BAFME) has been mapped to chromosome 8q24; however, genetic heterogeneity has been recently suggested. The authors report a clinical and electrophysiologic study of two Italian BAFME families showing linkage to chromosome 2p11.1-q12.2. Their report supports the evidence of non-Japanese families with BAFME and suggests a possible allelism with the recently described autosomal dominant cortical myoclonus and epilepsy syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
92
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(96 citation statements)
references
References 9 publications
3
92
0
Order By: Relevance
“…However, as opposed to our findings in the South African patients, photosensitivity appears to be common in both FAME and ADCME. 4,5,[7][8][9] In FAME, MRI is generally reported to be normal, 6,9 whereas cerebellar atrophy, ranging from mild to severe, was found in 8 of 10 patients from the two families reported here. Mild cerebellar atrophy on MRI was seen in two of four patients in a Dutch family with FAME, and a 68-year-old patient from this family had cerebellar degeneration at autopsy.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…However, as opposed to our findings in the South African patients, photosensitivity appears to be common in both FAME and ADCME. 4,5,[7][8][9] In FAME, MRI is generally reported to be normal, 6,9 whereas cerebellar atrophy, ranging from mild to severe, was found in 8 of 10 patients from the two families reported here. Mild cerebellar atrophy on MRI was seen in two of four patients in a Dutch family with FAME, and a 68-year-old patient from this family had cerebellar degeneration at autopsy.…”
Section: Discussionmentioning
confidence: 60%
“…[4][5][6]8,9,17 Compared with the disease in the South African families, the seizures associated with FAME may occur at a later age. 6,8,17 The EEG background is normal in ADCME and some family members with FAME have normal EEGs, 6,9,18 whereas abnormal EEG backgrounds and abundant polyspike discharges were the rule in the patients described in this report. However, as opposed to our findings in the South African patients, photosensitivity appears to be common in both FAME and ADCME.…”
Section: Discussionmentioning
confidence: 99%
“…A genetic locus for generalized epilepsy with febrile seizures plus (GEFS + ) was located at 2p24 (Audenaert et al 2005). A locus for benign adult familial myoclonic epilepsy (BAFME) is known to map at 2p11.1-q12.2 (Guerrini et al 2001;Labauge et al 2002;de Falco et al 2003;Madia et al 2008). FEB3, a locus for febrile seizures is known to map at the 2q23-q24 region (PeiVer et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Historically, various names have been given to the syndrome that show cortical myoclonic tremor and epilepsy: hereditary tremor with epileptiform seizures, 3 heredofamilial tremor and epilepsy, 4 cortical tremor, 5 familial essential myoclonus and epilepsy, 6 BAFME, 1 familial adult myoclonic epilepsy (FAME), 7 familial benign myoclonus epilepsy of adult onset, 8 familial cortical tremor with epilepsy, 9 autosomal dominant cortical myoclonus and epilepsy 10 and familial cortical myoclonic tremor with epilepsy (FCMTE). 11 Previous genetic studies, including our earlier report, 2 identified three different chromosomal loci, 8q 2,12 (BAFME, FCMTE1), 2p 10,13,14 (FCMTE2) and 5p 15 (FCMTE3) in Japanese, Italian and French pedigrees, respectively. The European patients seemed to show a more progressive disease course than Japanese patients.…”
Section: Introductionmentioning
confidence: 86%